Percutaneous endoscopic lumbar discectomy for lumbar disc herniation. (November 2016) - Li, Xinhua; Han, Yingchao; Di, Zhi; Cui, Jian; Pan, Jie; Yang, MingJie; Sun, Guixin; Tan, Jun; Li, Lijun
Highlights: Percutaneous endoscopic lumbar discectomy (PELD) results in better clinical outcomes compared to standard discectomy (SD). PELD could be viewed as a sufficient and safe supplementation and alternative to SD. More high-quality randomized controlled trials using sufficiently large sample sizes are required. Abstract: This study aims to compare the advantages and disadvantage of percutaneous endoscopic lumbar discectomy (PELD) and standard discectomy (SD) for the treatment of lumbar intervertebral disc herniation (LDH). We searched in MEDLINE, EMBASE, PubMed, Web of Science and Cochrane databases for relevant trials that compare PELD and SD for the treatment of LDH. The Cochrane Collaboration's Revman 5.3 software was used for data analyses. This meta-analysis compiled 1301 cases from four random controlled trials and three retrospective studies. Compared with SD, PELD showed a shorter operative time (mean difference (MD) = −18.68, 95% confidence interval (CI): −24.92 to −12.43; p  < 0.00001), less blood loss (MD = −64.88, 95% CI: −114.51 to −15.25, p  < 0.0001), shorter hospital stay (MD = −3.51, 95% CI: −4.93 to −2.08, p  < 0.00001), and shorter mean disability period (MD = −34.34, 95% CI: −53.90 to −14.77, p  < 0.006). However, there were no significant differences in the visual analogue scale (VAS) scores at the final follow up (MD = −0.23, 95% CI: −0.53 to 0.07, p  = 0.14), Macnab criteria at the final follow up (MD = 1.04, 95% CI: 0.72 to 1.50, p  = 0.82), complications (RR = 0.76, 95% CI: 0.40 to 1.43, p  = 0.39), recurrence rate (risk ratio (RR) = 1.00, 95% CI: 0.61 to 1.64, p  = 1) and reoperation rate (RR = 1.40, 95% CI: 0.90 to 2.16, p  = 0.13). In conclusion, despite PELD showing significant benefit in short term outcomes such as hospital course and mean disability period, similar clinical efficacy and long term outcomes were observed when compared to SD. Therefore, we suggest that PELD can be a feasible alternative to the conventional posterior approach for the LDH depending on surgeon preference and indication. High-quality randomized controlled trials with sufficient large sample sizes necessary further confirm these results.